The Effect of Fluid Velocity and Zig Zag Filter Foam Filler Distance on the Effectiveness of Cooling Tower - Andrea Setiawan; A’rasy Fahruddin (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the effect of fluid velocity and the distance between the zig zag filter on the cooling tower by varying the distance between the zig zag bio filter foam. In this study, bio filter foam material was used in a zig zg shape using wire mesh where the distances tested were 5cm, 10cm, and 15cm. Then the water is heated using a heater until it reaches a temperature of 40ºC and then the water is flowed up by a pipe using a pump and removed using a nozzle, then the hot water will go down to the reservoir by passing the bio filter foam arrangement that has been installed with a distance of 5cm , 10cm, and 15cm. Where there is also a drain valve that is done, namely a closed faucet and also an open kran and fully open faucet. A good cooling value is shown at a distance of 5 cm where the average temperature difference is 3.47 C and the effectiveness is 26.67%.